2018
DOI: 10.1016/j.engstruct.2018.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the combined effect of dowel misalignment and cyclic wheel loading on dowel bar performance in JPCP

Abstract: A number of previous studies indicated that the joint lockup due to misalignment and looseness of dowel bars may cause joint distress in Jointed Plain Concrete Pavement (JPCP). This article reports a detailed experimental investigation of pull-out load and joint lockup due to dowel misalignment; and dowel looseness caused by the combined effect of misalignment and cyclic traffic load. The test slabs were supported on steel beams with an appropriate amount of vertical stiffness so as to incorporate the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This thickness was chosen based on the diameters of the dowels available for testing. Therefore, we considered sample dimensions that were comparable to those in some previous studies, including Al-Humeidawi et al (2014) [12] in which specimens were used that were very similar in size to our specimens, which were 900900200 mm. In general, the sample dimensions were acceptable for the frame and tank capabilities in the laboratory.…”
Section: Tested Specimensmentioning
confidence: 98%
See 2 more Smart Citations
“…This thickness was chosen based on the diameters of the dowels available for testing. Therefore, we considered sample dimensions that were comparable to those in some previous studies, including Al-Humeidawi et al (2014) [12] in which specimens were used that were very similar in size to our specimens, which were 900900200 mm. In general, the sample dimensions were acceptable for the frame and tank capabilities in the laboratory.…”
Section: Tested Specimensmentioning
confidence: 98%
“…The specimens were placed over the subbase layers in the middle of the container then, the load was applied using a hydraulic jack on a steel plate with dimensions of 300×300×50 mm to ensuring that the load is distributed over an area greater than the area of the load cell, which has a diameter of 100 mm to avoid penetration of the specimens, as shown in Fig. (12). For each dial gauge, a unique arrangement was designed to ensure that it remained in its exact location and to ensure proper readings.…”
Section: Test Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding widely used jointed precast concrete pavement (JPrCP) systems, their performances primarily depend on the pavement joint design (Tayabji et al 2013, Smith andSnyder 2019). To reduce the stress and deflection induced in the loaded pavement slab, epoxycoated steel dowel bars are commonly used as load transfer devices to transfer a portion of load to the unloaded slab (Murison et al 2005, Porter and Pierson 2007, Shoukry et al 2007, Tayabji et al 2013, Al-Humeidawi and Mandal 2014, El-Maaty et al 2017, Al-Humeidawi and Mandal 2018, Keymanesh et al 2018, Smith and Snyder 2019. However, in spite of widespread use for nearly a century (Teller and Cashell 1959), there are still critical issues that deteriorate the joint performance under wheel loads.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by the authors showed that Glass Fibre reinforced Polymer (GFRP) dowels provide adequate load transfer efficiency under static and cyclic load, and produce significant reduction in the pull-out load especially in the presence of dowel misalignment. Therefore, these dowel bars were used in the current investigation [8][9][10][11][12]. As GFRP dowels have very low frictional and bond stress with concrete, it is suitable for the current study to clarify the dowel misalignment effect on the pull-out load.…”
Section: Introductionmentioning
confidence: 99%